Çocuklarda eğitim amaçlı oyunun diyabetin akut komplikasyonları ve sağlık okuryazarlığına etkisi: randomize kontrollü çalışma - Yeşil, Fatma (My University, 2024)
Amaç: Bu çalışmanın amacı tip 1 diyabet tanısı alan 8-12 yaş arası çocuklarda eğitim amaçlı geliştirilen kutu oyununun diyabetin akut komplikasyonları ve sağlık okuryazarlığına etkisinin incelenmesi amacıyla randomize kontrollü deneysel bir araştırma geliştirmektir. Gereç ve Yöntem: Araştırma iki aşamada gerçekleştirilmiştir. Birinci aşama: Çocuklar için Tip 1 Diyabetin Akut Komplikasyonlarına Yönelik Sağlık Okuryazarlığı Ölçeği (DSOYÖ) psikometrik özelliklerinin geliştirilmesi ve test edilmesi amacıyla metodolojik olarak gerçekleştirilen araştırmanın evrenini Haziran-Ekim 2022 tarihleri arasında bir eğitim ve araştırma hastanesi pediatrik diyabet polikliniğinde tedavi gören 8-12 yaş arası en az bir yıllık diyabet tanısı olan tip 1 diyabetli çocuklar oluşturmuştur. Bu çalışma 222 diyabetli çocukla tamamlanmıştır. İkinci aşama: Randomize kontrollü deneysel tipte gerçekleştirilen araştırmanın evrenini Ocak-Mayıs 2023 tarihleri arasında iki eğitim ve araştırma hastanesi pediatrik diyabet polikliniğinde tedavi gören en az bir yıllık diyabet tanısı olan 8-12 yaş arası tip 1 diyabetli çocuklar oluşturmuştur. Çalışmada diyabet sağlık okur yazarlığı kutu oyunu (DİSOY) oynayan grup (n=38) ve standart eğitim alan grup (n=37) olmak üzere toplam 75 tip 1 diyabetli çocuk örneklemi oluşturmuştur. Araştırmada randomizasyon yöntemi kullanılmıştır. Bulgular: DSOYÖ, diyabetin akut komplikasyonları ve sağlık okuryazarlığı hakkında bilgi içeren 19 madde ve 3 faktörden oluşmaktadır. Deney ve kontrol grupları arasında yapılan karşılaştırmada girişim öncesinde çocukların diyabet sağlık okuryazarlık düzeyleri yönünden anlamlı fark yoktur, buna karşıngirişim sonrası 1. ay ve 3. ay izlemlerde deney grubundaki çocukların diyabet sağlık okuryazarlık düzeyleri kontrol grubundaki çocuklardan anlamlı düzeyde daha yüksek bulunmuştur (p<0,05). Sonuç: Çocuklar için tip 1 diyabetin akut komplikasyonlarına yönelik sağlık okuryazarlığı ölçeği (DSOYÖ)18 maddeye sahip geçerli ve güvenilir bir ölçüm aracı olduğu kanıtlanmıştır. Diyabet sağlık okuryazarlığı kutu oyunu ile verilen eğitimin diyabetli çocukların diyabet akut komplikasyonları ve sağlık okuryazarlığını geliştirmede etkili olduğu kanıtlanmıştır. yabet, çocuklar, sağlık okuryazarlığı, sosyal öğrenme kuramı, kutu oyunu.

Objective: The aim of this study was to develop a randomised controlled experimental study to examine the effect of an educational board game on acute complications of diabetes and health literacy in children aged 8-12 years diagnosed with type 1 diabetes. Materials and Methods: The study was conducted in two phases. First phase: The population of the study, which was conducted methodologically to develop and test the psychometric properties of the health literacy scale for acute complications of diabetes for children with type 1 diabetes (DHLS), consisted of children with type 1 diabetes aged 8-12 years with a diagnosis of diabetes for at least one year who were treated in the paediatric diabetes outpatient clinic of a training and research hospital between June and October 2022. This study was completed with 222 children with diabetes. Second phase: The population of the randomised controlled experimental type study consisted of children aged 8-12 years with type 1 diabetes with a diagnosis of diabetes for at least one year who were treated in the paediatric diabetes outpatient clinics of two training and research hospitals between January and May 2023. In the study, a total of 75 children with type 1 diabetes, including the group playing diabetes health literacy box game (n=38) and the group receiving standard education (n=37), constituted the sample. Randomisation method was used in the study. Results: The health literacy scale for acute complications of diabetes for children with type 1 diabetes consists of 19 items and 3 factors including information about acute complications of diabetes and health literacy. In the comparison between the experimental and control groups, there was no significant difference in the diabetes health literacy levels of the children before the intervention, however, the diabetes health literacy levels of the children in the experimental group were found to be significantly higher than the children in the control group at the 1st month and 3rd month follow-ups after the intervention (p<0,05). Conclusion: The health literacy scale for acute complications of diabetes for children with type 1 diabetes was proven to be a valid and reliable measurement tool with 18 items. It was proved that the education given with the diabetes health literacy box game was effective in improving the acute complications of diabetes and health literacy of children with diabetes. Type 1 diabetes, children, health literacy, social learning theory, box game.
The impact of educational play on the acute complications of diabetes and health literacy in children: a randomised controlled study
Keywords: box game; children; Çocuk hastalıkları hemşireliği; çocuklar; health literacy; kutu oyunu; Pediatric nursing; sağlık okuryazarlığı; social learning theory; sosyal öğrenme kuramı; Tip 1 diyabet; Type 1 diabetes